Supply Chain Risk Assessment and Management for Mount Merapi Disaster Logistics Distribution - Jatiningsih, Maria Gratiana Dian; Finansia, Cici (Sebatik, 2025)
Mount Merapi is predicted to have small eruptions annually and larger eruptions every 7-8 years. This necessitates preparedness from all parties to face potential eruptions so that the impacts can be minimized. One important aspect to consider is the distribution of logistical assistance. The aim of this research is to assist BPBD Sleman in completing a contingency plan for Merapi eruption disasters. The findings from this research can help anticipate issues in the logistics distribution process, ensuring it is more even and timely if an eruption occurs in the future. This study employs the House of Risk (HOR) method, which consists of two stages. In the first stage, the focus is on identifying risk causes (risk agents) and determining priorities. The second stage involves establishing treatment actions to address priority risk agents based on the analysis from the first stage. The results indicate that the risk agents with the highest scores are inappropriate data sharing, refugees moving around, rough estimates of logistics needs, insufficient warehouse capacity, and lack of work supervision. The second-stage analysis produces mitigation plans to prevent these risk agents, one of which includes using real-time applications. To prevent the emergence of the identified risks, it is necessary to develop a real-time information system that can provide updates on the number of refugees.